Evaluation of peripheral blood neutrophil function in tumor-bearing dogs - LeBlanc, Casey J (Veterinary clinical pathology, 2010)
BACKGROUND: Peripheral blood neutrophils of untreated human cancer patients have been shown to have normal, increased, and decreased phagocytic activity, killing capacity, and/or oxidative burst activities